Pengaruh Financial Distress, Pergantian Auditor dan Manajemen Laba terhadap Audit Delay - Afifah Pujiyanti Romli; Dea Annisa (Universitas Pamulang, 2020)
This study aims to determine the influence of financial distress, auditor turnover and earnings management on audit delay in Mining Sector companies listed on the Indonesia Stock Exchange (2017-2019). This type of research is quantitative. The sample was selected based on the purposive sampling method, so that the samples obtained were 42 companies. The data analysis technique used is multiple linear regression analysis, with data processing using the SPSS 25.0 for window program. The results showed that simultaneously the variable financial distress, auditor turnover and earnings management have an effect on audit delay. Meanwhile, partially financial distress, auditor turnover and earnings management have an effect on audit delay Keywords: Financial Distress, Auditor Change, Earnings Management, Audit Delay